Risk factors of occupational stress among non-destructive testing radiographers in Saudi Arabia - Khalaf, Alsharafat Khalaf Sail (2018)
Introduction: The non-destructive testing field is one of the critical fields supporting the oil and gas industry in Saudi Arabia. Due to the working conditions experienced by the employees of this sector, especially radiographers, the conditions of the workplace affect them and cause considerable job stress. As such, there is a need to undertake an in-depth study of the association between occupational stress and the sources of stress. The aim of this study was to determine the association between workplace stressors, personal stressors, and occupational stress level among radiographers in a non-destructive testing company in Saudi Arabia.The methodology adopted is a cross-sectional study conducted at five non-destructive testing companies in Saudi Arabia. A total of 112 employees were selected as the sample. A questionnaire was used to determine the socio-demographic and occupational backgrounds.The social and psychological characteristics of the respondent’s job were determined using the JCQ (Job Content Questionnaire). Salivary alpha-amylase assay kit was used to analyse the salivary alpha-amylase levels as an indicator of occupational stress. The results showed that the response rate was 100%. Cronbach’s alpha coefficient for the English version of JCQ was acceptable (α = 0.70). The majority of the respondents were Indians (33.0%), followed by Filipinos (24.11%), Saudi Arabians (17.0%), Jordanians (16.1%), Pakistanis (6.3%), and others (3.6%). Most of the respondents were on night shift (60.7%) and worked overtime (72.3%). The mean value of salivary alpha amylase activity among workers was 72.34±11.39 U/ml during pre-shift and 94.09±15.95 U/ml post-shift. Paired sample t-test showed the mean exposed group differed significantly from the non-exposed group (t=8.48, df= 46, p<0.05; 95% Cl: 15.47 - 25.10).The prevalence of occupational stress among the exposed group was 88.0% and non-exposed group 58.0 %. The group who were exposed to heat stress had high prevalence of occupational stress level of 61.4%.This findings of this study showed that there was high prevalence of occupational stress among industrial radiographers.Workplace stressors associated with occupational stress among these workers suggest that the safety and health precautions of workers performing radiography wok are important and should be addressed.